Arthur's first sleepover - Brown, Marc Tolon (Boston : Little, Brown, 1994)
Rumors about sightings of an alien space ship create excitement when Arthur's friends come to spend the night.
2.4
K-3
K-3
Elem. School Library Collection
School Library Journal
Horn Book Starred
Keywords: Sleepovers -- Fiction; Aardvark -- Fiction; Arthur (Fictitious character : Brown) -- Fiction; Sleepovers -- Fiction; Aardvarks -- Fiction; Arthur (Fictional character : Brown) -- Fiction